Sacubitril-Valsartan Compared With Enalapril for the Treatment of Heart Failure: A Decision-Analytic Markov Model Simulation in China - Wu, Yue; Tian, Shuo; Rong, Peipei; Zhang, Fan; Chen, Ying; Guo, Xianxi; Zhou, Benhong (Frontiers in Pharmacology, 2020)
Objectives: Heart failure with reduced ejection fraction (HFrEF) is a major global health issue with considerable mortality, hospitalization rate and extreme expenditure. Nowadays, the prevalence of HFrEF is rising significantly in Asian countries. Due to the limited economic level, Asian countries are facing with even heavier socio-economic burden than western, especially in some developing countries with large population, such as China. In treatment of HFrEF, Sacubitril-valsartan is now stated as a class I recommendation in major guidelines. However, the pharmacoeconomic evaluation of this new drug in China is not reported. In this research, we conducted a cost-effectiveness analysis of sacubitril/valsartan versus enalapril, based on the China’s national price negotiation, to fully assess the expected costs and benefits of sacubitril-valsartan in China. Method: A Markov model was constructed to estimate long-term clinical and economic outcomes of Sacubitril-valsartan versus enalapril for heart failure patients with reduced ejection fraction in China over a lifetime of 10-year horizon. Primary model outcomes were total costs and quality-adjusted life years (QALYs) for sacubitril/valsartan versus enalapril as well as the incremental cost-effectiveness ratio (ICER). Results：Treatment with sacubitril-valsartan was predicted to yield 4.25 QALYs at the cost of $4684.25. The use of enalapril yielded 4.00 QALYs at the cost of $4014.47. Compared to enalapril, Sac-val associated with a gain of 0.25 QALYs, resulting in an ICER of $ 2679.12 per QALY. Deterministic sensitivity analysis showed that results remained robust. Probabilistic sensitivity analysis suggested the probability that sacubitril-valsartan was cost-effective was 99.9%, when $10,276, a GDP per capita of China, was applied as willingness-to-pay thresholds. Conclusion: From Chinese patients’ perspective, sacubitril-valsartan is a cost-effective treatment for HFrEF compared with enalapril. This finding could be helpful to guild the use of sacubitril/valsartan in China. Furthermore, decision makers could refer to these meaningful results to discuss the value and position of novel ANRI in the future.